Computerized system for determination of the psychological readiness of the civil aviation students in emergency situations - Selivanova, K.; Solovyova, O.; Semerenko, Y. (Stockholm, Sweden, 2020)
To ensure a complex analysis of indicators of the psychophysiological state of the civil aviation student to assess his preparedness for emergency situations, a psychodiagnostic model and computerized system were developed. This model consists of the main components that are blocks: functional, cognitive-perceptual, psychophysiological, individual-typological and motivational. These are separate methods and tests for individual assessment of certain components of the psychophysiological and emotional state of the student pilot. The obtained results show the need for using integrated indicators in assessing the preparation of pilots for emergencies. The designed system allows for solving this issue.
Keywords: psychodiagnostics; computerized system; civil aviation; emergency situations; students